Disfunkcija sramnične zrasti med nosečnostjo in po porodu - Saltirova, Saška (Obzornik zdravstvene nege, 2009)
Introduction: Timely diagnosis and appropriate conservative treatment can improve the quality of life of women suffering from symphysis pubis dysfunction. The aim of the study was to determine to what extent the specialists in gynaecology and obstetrics follow the new European guidelines in diagnosing and treatment of this condition. Methods: Invited to participate in the study were 44 invited obstetricians and gynaecologists, employed in the University Clinical Centre, Ljubljana, Gynaecology Clinic and basic units of the Community Health Centre, Ljubljana. Results: Survey data were collected from 35 (79 %) respondents, aged 49,2 9,65. Analysis of the findings shows that in year 2008 the majority of the doctors treated women with symphysis pubis dysfunction during pregnancy (3,5 women in average), between 25-35 years of age. The most common problem reported by the women was pain during walking (69 %). The pain most frequently occurred in the symphysispubis area (59,6 %), in the symphysis pubis area radiating into the groins, hip joints or the lower extremities (21,3 %) and in the sacroiliac joints, the perineum and the lower back (12,8 %). The results also indicate that the diagnosis of symphysis pubis dysfunction was in larger part reached through clinical tests (41,9 %) and ultra sound examination during pregnancy (23,3 %) and x-ray examination (39,5 %), ultra sound examination (23,3 %) and clinical tests (20,9 %) after the delivery. All of the respondents recommend the use of a pelvic belt and 90,9 % of them would propose also health education for women diagnosed with symphysis pubis dysfunction. 24 (88,9 %) out of 27 gynaecologists employed at the Gynaecology Clinic, Ljubljana opined that symphysis pubis dysfunction occurs or deteriorates during delivery and 55.6 % of the respondents were not aware of alternative labour and delivery position options. Discussion and conclusion: The study research findings evidence that the respondents are familiar with/recognise the signs and symptoms of symphysis pubis dysfunction. However, they consider the symphysis pubis dysfunction with the accompanying pain during pregnancy a normal physiologic phenomenon. They are less knowledgeable of the possible diagnosticand recommended therapeutic procedures. There is a need for more in-depth knowledge and awareness of the issue in order to timely diagnose and treat women with symphysis pubis dysfunction resulting in their better quality of life.
Keywords: diagnostika; disfunkcija sramnične zrasti